2018
DOI: 10.3892/ol.2018.9672
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of stage�II‑IV upper‑tract urothelial carcinoma and adjuvant chemotherapy for locally advanced cancer

Abstract: The present retrospective study aimed to examine the outcomes of stage II-IV upper-tract urothelial carcinoma (UTUC) and determine whether adjuvant chemotherapy is a beneficial treatment for patients with locally advanced UTUC (specifically, stage III-IV). The analysis included 126 patients with muscle-invasive UTUC who were treated between June 2003 and June 2012. All patients underwent laparoscopic or open nephroureterectomy and bladder cuff excision. Overall survival (OS), disease-free survival (DFS), dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Although UTUC is relatively uncommon compared with bladder cancer (5–10% of UCC) ( 3 ), a three- to four-fold higher rate of muscle invasion at diagnosis ( 4 ) leads to poor prognosis of patients. In fact, the 5-year survival rate is < 50% for patients with T2-T3 and < 10% for patients with T4 UTUC, which are substantially lower than the average survival rates in other cancers ( 5 ). Therefore, studies focused on identification and stratification of risk factors via orthogonal approaches, including genetic analysis and molecular subtyping to enhance survival outcomes ( 3 , 6 11 ).…”
Section: Introductionmentioning
confidence: 82%
“…Although UTUC is relatively uncommon compared with bladder cancer (5–10% of UCC) ( 3 ), a three- to four-fold higher rate of muscle invasion at diagnosis ( 4 ) leads to poor prognosis of patients. In fact, the 5-year survival rate is < 50% for patients with T2-T3 and < 10% for patients with T4 UTUC, which are substantially lower than the average survival rates in other cancers ( 5 ). Therefore, studies focused on identification and stratification of risk factors via orthogonal approaches, including genetic analysis and molecular subtyping to enhance survival outcomes ( 3 , 6 11 ).…”
Section: Introductionmentioning
confidence: 82%
“…In 2017, Nakagawa et al reported that adjuvant chemotherapy improved CSS in a cohort of 109 patients with advanced-stage UTUC after RUN [13]. In 2019, Huang et al also demonstrated the therapeutic benefit of adjuvant chemotherapy in stage II-IV local UTUC [14].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, carboplatin was a useful alternative solution when cisplatin was contraindicated and not at the expense of efficacy [18]. Chang et al also supported the efficacy of adjuvant chemotherapy with carboplatin in patients with advanced UTUC [14]. In contrast, Leow et al compared non-cisplatin-based or cisplatin-based adjuvant chemotherapy after RUN and found no survival benefit for non-cisplatin-based regimens [19].…”
Section: Discussionmentioning
confidence: 99%
“…NCCN guidelines either lack treatment recommendations for stage IV nmUTUC (T4N0M0, TanyN1-2M0) or recommend CT alone for mUTUC treatment ( 7 ). Although a few studies have reported the survival benefit of CT + NU for locally advanced UTUC compared with NU alone, few have analyzed this in patients with stage IV nmUTUC ( 6 , 9 , 15 17 ) or mUTUC ( 2 , 8 , 13 ). Our study demonstrated that compared with CT alone, their combination confers OS benefits to patients with stage IV nmUTUC or mUTUC.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with UTUC have a lower OS than do those with bladder urothelial cancer (BUC) because >60% of patients with UTUC present with invasion at diagnosis, whereas only 15%–25% of patients with BUC present with invasion at diagnosis ( 3 , 4 ). Furthermore, the prognosis of patients with T4 UTUC is poor, with the 5-year OS being <10% ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%